2019
DOI: 10.3389/fimmu.2019.01898
|View full text |Cite
|
Sign up to set email alerts
|

MALT1 Proteolytic Activity Suppresses Autoimmunity in a T Cell Intrinsic Manner

Abstract: MALT1 is a central signaling component in innate and adaptive immunity by regulating NF-κB and other key signaling pathways in different cell types. Activities of MALT1 are mediated by its scaffold and protease functions. Because of its role in lymphocyte activation and proliferation, inhibition of MALT1 proteolytic activity is of high interest for therapeutic targeting in autoimmunity and certain lymphomas. However, recent studies showing that Malt1 protease-dead knock-in ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 93 publications
(125 reference statements)
5
52
1
Order By: Relevance
“…Although the reduced frequency of Tregs in Malt1PD mice may on its own be sufficient to drive the inflammatory disease, the absence of Malt1 protease function in Tregs may also impact additional Treg immunoregulatory mechanisms critical for the maintenance of immune homeostasis in vivo. To this point, four recent studies provided critical novel insights into the functional consequences of the disruption of the CBM complex in Foxp3 + Tregs via the genetic deletion of CARD11, BCL10, or MALT1 or via the genetic inactivation of the MALT1 protease (85)(86)(87)(88). In line with our findings, Cheng et al reported that Malt1PD Tregs display an overall normal in vitro suppression activity, whereas Rosenbaum et al suggested a partial reduction in in vitro suppressive activity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although the reduced frequency of Tregs in Malt1PD mice may on its own be sufficient to drive the inflammatory disease, the absence of Malt1 protease function in Tregs may also impact additional Treg immunoregulatory mechanisms critical for the maintenance of immune homeostasis in vivo. To this point, four recent studies provided critical novel insights into the functional consequences of the disruption of the CBM complex in Foxp3 + Tregs via the genetic deletion of CARD11, BCL10, or MALT1 or via the genetic inactivation of the MALT1 protease (85)(86)(87)(88). In line with our findings, Cheng et al reported that Malt1PD Tregs display an overall normal in vitro suppression activity, whereas Rosenbaum et al suggested a partial reduction in in vitro suppressive activity.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with this, both groups observed that the genetic inactivation of the Malt1 protease function selectively in Foxp3 + Tregs is sufficient to drive a severe IPEX-like inflammatory disease. In line with this, Demeyer et al (86) reported that mice characterized by a T cell-restricted Malt1 protease deficiency develop an IPEX-like syndrome similar to the one reported in mice with a systemic Malt1 protease defect. Additional data involving the use of Malt1PD Tregs or WT Tregs treated with a MALT1 inhibitor suggest that inhibition of the Malt1 protease function results in defective expression of CTLA4, IL-10, and TGF-b (85,88).…”
Section: Discussionmentioning
confidence: 57%
“…In line with this, T cell-restricted inactivation of MALT1 protease is sufficient to cause an IPEXlike pathology similar to the one observed in full-body MALT1 PD animals (27). Of note, using MALT1 PD Treg cells or WT Treg cells treated with a MALT1 inhibitor, various groups suggested that impairment of MALT1 protease function in Tregs leads to defective upregulation of several molecules associated with Treg suppressive activity, such as CTLA-4, IL-10, and TGF-β (26,27,29). Overall, these studies indicate that CBM components including MALT1 protease function are critical to maintain the optimal suppressive function and identity of Tregs in vivo.…”
Section: Introductionsupporting
confidence: 69%
“…Genetic deletion of CARD11, BCL10, or MALT1, as well as the genetic inactivation of the MALT1 protease selectively in Foxp3 + Tregs was associated with Treg dysfunction in vivo and development of an IPEXlike disease (26,28,29). In line with this, T cell-restricted inactivation of MALT1 protease is sufficient to cause an IPEXlike pathology similar to the one observed in full-body MALT1 PD animals (27). Of note, using MALT1 PD Treg cells or WT Treg cells treated with a MALT1 inhibitor, various groups suggested that impairment of MALT1 protease function in Tregs leads to defective upregulation of several molecules associated with Treg suppressive activity, such as CTLA-4, IL-10, and TGF-β (26,27,29).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation